How to Avoid Human-Animal Dichotomy and Become Ethical - Kathet, Gunja (Interdisciplinary Journal of Management and Social Sciences, 2021)
Anthropomorphizing is not simply lending human attributes to nonhuman animals; but in the very act of lending, there is taming and domesticating of animals. This paper in the light of Critical Animal Studies (CAS) argues that the companion/ pet species are the result of  human intervention in the wilderness, taking away the natural life of cats, dogs, horses, and so many others; then, caging or leashing them, thus suspending their rights, even while proliferating their population. While feeding them "properly," proper to human standards, humans have weakened the pet species' immunity and aggravated their vulnerability. Since it is, at the end, for the pleasure and wellbeing of human, anthropomorphism is also anthropocentrism.